IMPLEMENTASI METODE SENTRA PERSIAPAN DALAM MENGEMBANGKAN KECERDASAN VERBAL LINGUISTIK ANAK USIA DINI - ellyana ilsan eka putri; Rosdiana Dewi; Imam Wahyono (Tarbiyatuna Kajian Pendidikan Islam, 2020)
This study aims to describe: 1) the implementation of centers of preparation in developing verbal linguistic intelligence, 2) supporting factors and obstacles to the implementation of preparation centers in developing verbal linguistic intelligence. This type of research is a qualitative research method with the principal subject of research, teachers, students aged 5-6 years. Data collection is done using the method of observation, interviews and documentation. The results showed that: 1) the implementation of the method of preparation center in developing verbal linguistic intelligence was carried out with 3 stage, 2) supporting factors in the implementation of preparation centers, namely: a) the media provided varies or the availability of complete facilities and infrastructure, b) learning based on age classification c) programmed learning. while the inhibiting factors are: a) the condition of the guardian of the student who does not understand the method of preparation center, b) the mood of the changing child c) the media that do not support the difficult theme d) not all teachers graduate from PAUD.